Let's Learn Mandarin Grammar / Lim Hong-Rui, Lim Zhe-Yu and Low Hiang Loon - Lim, Hong-Rui; Lim, Zhe-Yu; Low, Hiang Loon (2021)
Mandarin courses for non-native speakers are offered widely in Malaysia's higher institutions. In order to help Mandarin learners to master the language, the aspect of Mandarin grammar should play an important role in the process of learning. Unfortunately, Mandarin textbooks produced by local authors have not given emphasis on grammatical teaching. The "Introductory Mandarin Level 1" used by a vast number of learners in Malaysia has provided explanations only for 2 grammatical points in the entire Mandarin textbook. To overcome the insufficient Mandarin grammar learning among Malaysian Mandarin learners, we proposed that Mandarin grammatical point videos should be developed to meet Mandarin learners' language needs. Four Mandarin grammatical point videos created by Powtoon animation were released to students for evaluation purposes. Very encouraging feedback was given by 60 Mandarin learners. Majority of the respondents (91.6%) admitted that a Mandarin textbook for non- native speakers should include sufficient grammatical points to help learners understand the rules of Mandarin. Furthermore, 90% of the respondents 'agreed' (45%) & 'strongly agreed' (45%) that the videos are effective, while 96.7% of respondents deemed that the innovation is "useful" (46.7%) and "very useful" (50%) to guide elementary Mandarin learners. The development of the Mandarin grammatical point video is a novelty in the field of teaching and learning Mandarin as a foreign language in Malaysia. The efficacy is evidenced by respondents' claims where 86.7% of respondents "agreed" (51.7%) and "strongly agreed" (35%) that they will master Mandarin grammatical points better through audio-visual methods. With all positive feedback given by the respondents including 25% of them have committed ("definitely yes") to purchase the proposed e-module of 50 grammatical points at RM10, we can generalise that about 25% of Mandarin learners in Malaysia will be keen to purchase the product, and therefore, the innovation has projected great commercial potential.